Kahoot Analysis as a Game Media-Based Learning in Early Childhood Education - khoiril fatekhah fatekhah; Isnaini Naffi'an; Siti Munawaroh (Schola, 2026)
This study aims to analyze the use of Kahoot as a game-based learning medium in Early Childhood Education (PAUD). Kahoot is an interactive quiz platform that combines elements of education and entertainment so that it suits the characteristics of early childhood learning. The research method used is a literature study by reviewing various scientific articles, books, and research related to the use of digital media, game-based learning, and early childhood characteristics. The results of the study show that Kahoot has a number of advantages, including increasing children's learning motivation, engagement, and concentration through attractive visual displays, sounds, animations, and a healthy competitive atmosphere. Kahoot also makes it easier for teachers to deliver material in a fun way and encourages active participation of children, even for children who are usually passive. However, the implementation of Kahoot in PAUD faces several challenges, such as limitations in children's literacy and motor skills, the need for intensive assistance from teachers and parents, and the limited technological facilities in several PAUD institutions. To overcome these challenges, teachers are advised to formulate questions based on images and sounds, involve parents, and carry out activities in small groups with a duration adjusted to the child's attention span. With proper planning, Kahoot has proven to have the potential to be a fun, interactive, and effective learning medium for introducing basic concepts to early childhood.